Solomon Islands : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2018)
This Selected Issues paper sets out options to demonstrate how the authorities could supplement their cash balance target and public debt limit with an anchor to help discipline annual budget decisions. The paper introduces the current fiscal framework and effective fiscal rules based on international experiences, including the characteristics of each rule. It also discusses the need for a new fiscal anchor, given high revenue volatility, high infrastructure needs, and the country's exposure and vulnerability to natural disasters. Contingency warrants for unforeseen expenditures, including from natural disasters, should be included in the budget in line with international best practices. Furthermore, if a disaster does not occur, this allocation could be saved in a contingency fund for natural disasters, which would enable swift disbursement in the aftermath of the disaster. The fund would be set up once fiscal buffers have been rebuilt. The IMF Staff suggests a target for the overall fiscal deficit of 1.5 percent of gross domestic product as a possible fiscal anchor, which would strike a balance between safeguarding debt sustainability and addressing the severe infrastructure gap.